2017
DOI: 10.18632/oncotarget.15595
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme 2 overexpression protects against doxorubicin-induced cardiomyopathy by multiple mechanisms in rats

Abstract: Angiotensin-converting enzyme 2 (ACE2) is considered a potential therapeutic target of the renin-angiotensin system (RAS) for the treatment of cardiovascular diseases. We aimed to explore the effects of ACE2 overexpression on doxorubicin-induced cardiomyopathy in rats. Rats were randomly divided into treatment and control groups. The rats of treatment group were injected intraperitoneally with 6 doses of doxorubicin (2.5 mg/kg) within a period of two weeks. Two weeks after the initial injection of doxorubicin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 55 publications
3
26
1
Order By: Relevance
“…We found little change in p-AMPK/AMPK in the lung tissue from both ACE2 S680D knock-in and ACE2 2/2 mice (data not shown). Thus, the putative feedback loop regulation of AMPK-ACE2 reported by Ma and colleagues was not apparent in our experimental system (53).…”
Section: Discussioncontrasting
confidence: 52%
“…We found little change in p-AMPK/AMPK in the lung tissue from both ACE2 S680D knock-in and ACE2 2/2 mice (data not shown). Thus, the putative feedback loop regulation of AMPK-ACE2 reported by Ma and colleagues was not apparent in our experimental system (53).…”
Section: Discussioncontrasting
confidence: 52%
“…As a core enzyme in the metabolism of AngII, ACE2 directly regulates the levels of AngII and Ang(1-7). ACE2 is accepted as an Ang(1-7) marker and considered to be a feasible therapeutic target of the RAS [26,122]. Based on current researches, ACE2 and AMPK have closed relations.…”
Section: Ace2 and Ampkmentioning
confidence: 99%
“…In Na et al's [144] study, vinegar and acetic acid decreased serum renin and ACE activities, AngII and aldosterone concentration in SHRs, simultaneously, elevated AMP/ATP ratios and the phosphorylation of AMPK, PPARγ, co-activator-1α (PGC-1α) [144]. In 2017, one study demonstrated that ACE2 overexpression down-regulated the mortality of rats with doxorubicin-induced cardiomyopathy [122]. Its mechanism may involve activation of the AMPK and PI3K-AKT pathways, inhibition of ERK pathway and TGF-β1 expression [122].…”
Section: The Balance Of Ras and Ampkmentioning
confidence: 99%
See 1 more Smart Citation
“…For direct cardiac function evaluation, hemodynamic measurements were recorded and calculated with a pressure volume catheter (SPR-838, Millar Instruments, Houston, TX, USA) using the Millar pressure-volume system (MPVS-300, Millar Instruments) as previously described (Malka et al, 2016). Echocardiographic measurements were performed using a 7.5-MHz phased-array transducer connected to a sector scanner (SONOS 7500, Philips Medical Systems, Andover, MA) as previously described (Ma et al, 2017). Echocardiography cines were obtained according to the American Society of Echocardiography guidelines (Arias et al, 2013).…”
Section: Cardiac I/r Model In Ratsmentioning
confidence: 99%